PELATIHAN KADER INOVASI DASHAT (DAPUR SEHAT ATASI STUNTING) DI KABUPATEN TEBO, BUNGO, DAN KERINCI TAHUN 2022 - Ummi Kalsum; Nutriani Rahma Baitilla; Guspianto Guspianto (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2023)
ABSTRACT Stunting is still a public health problem in Indonesia, as well as in Jambi Province. The incidence of stunting in toddlers in Jambi Province reached 30.2% (2018). Even though there is a decrease in stunting in 2021 based on a survey of the nutritional status of toddlers to 22.4%, it has not yet reached the target set by SDG's. DASHAT innovation cadre training activities in the three districts where the assistance is located, namely Tebo, Bungo, and Kerinci Regencies. Participants involved in this activity were 50 people in each district consisting of five trained cadres from 10 villages where the focus was on stunting management. The number of training participants was 150 cadres in 3 districts. The majority of training participants were women (94.8%), the majority were early adulthood (26-35 years) namely 37.9%. The average knowledge score before the training was 5.19 and increased to 5.45 after the training. There is an effect of the training on the level of knowledge of the participants before and after the training (P-value = 0.031). Participants who had good knowledge before training was 45.5%, increasing to 53.0%. There is an increase in understanding and skills as well as motivation in each participant who is trained. It is hoped that the training participants will be able to apply what they get during the training to the community and be able to become a driving force so that the acceleration of stunting reduction in the village area of each cadre can be realized as expected. ABSTRAK Stunting masih menjadi masalah kesehatan masyarakat di Indonesia, demikian pula di Provinsi Jambi. Kejadian stunting pada balita di Provinsi Jambi mencapai 30,2% (2018). Meskipun ada penurunan stunting di pada tahun 2021 berdasarkan survey status gizi balita menjadi 22,4%, namun belum mencapai target yang ditetapkan SDG’s. Kegiatan pelatihan kader inovasi DASHAT di tiga Kabupaten yang menjadi lokasi pendampingan yaitu Kabupaten Tebo, Bungo, dan Kerinci. Peserta yang terlibat dalam kegiatan ini adalah 50 orang di setiap Kabupaten yang terdiri dari masing-masing lima orang kader yang dilatih dari 10 desa lokus fokus penanganan stunting. Jumlah peserta pelatihan adalah 150 kader di 3 Kabupaten. Peserta pelatihan mayoritas perempuan (94,8%), usia terbanyak adalah dewasa awal (26 – 35 tahun) yaitu 37,9%. Rata-rata skor pengetahuan sebelum pelatihan adalah 5,19 dan meningkat menjadi 5,45 setelah pelatihan. Terdapat pengaruh pelatihan terhadap tingkat pengetahuan peserta sebelum dan sesudah pelatihan (P-value = 0,031). Peserta yang memiliki pengetahuan baik sebelum pelatihan adalah 45,5%, meningkat menjadi 53,0%. Terdapat peningkatan pemahaman dan keterampilan juga motivasi pada diri setiap peserta yang dilatih. Diharapkan peserta pelatihan mampu menerapkan apa yang diperoleh saat pelatihan kepada masyarakat serta mampu menjadi penggerak agar percepatan penurunan stunting di wilayah desa masing-masing kader dapat terwujud sesuai dengan yang diharapkan.